Rechte des Körpers Juristische, philosophische und theologische Perspektiven - Priesemuth, Florian; Frey, Michael; Berger, Christian (De Gruyter, 2022)
The volume asks about the role of the body in law. Representatives of philosophy, theology, and jurisprudence examine the physical, material, or natural (pre-)conditions of law, which law does not cover or covers only to a degree.